A high-frequency adhesive for flexible copper-clad laminate and preparation method thereof

By using modified benzoxazine, bismaleimide and modified polyimide resin compositions, combined with glass wool fibers and mesoporous silica fillers, high-frequency adhesives were prepared, and the problems of high dielectric constant and poor heat resistance of flexible copper clad plates were solved, and the effects of low dielectric constant, low dielectric loss and high thermal stability were achieved.

CN119592293BActive Publication Date: 2025-05-09HUBEI HENGCHI ELECTRONIC TECH CO LTD
View PDF 4 Cites 0 Cited by

Patent Information

Application Number
CN202510146935.9
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2025-02-11
Publication Date
2025-05-09
Estimated Expiration
2045-02-11

AI Technical Summary

Technical Problem

The existing flexible copper clad plate has a high dielectric constant and poor heat resistance, resulting in high dielectric loss and short service life.

Method used

Modified benzooxazine, bismaleimide and modified polyimide are used as resin compositions, combined with glass wool fibers and mesoporous silica as fillers, and high-frequency adhesives are prepared.

Benefits of technology

It significantly reduces the dielectric constant and dielectric loss of high-frequency adhesives, improves its thermal stability and dimensional stability, and thus extends the service life of flexible copper clad plates.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure SMS_1
    Figure SMS_1
Patent Text Reader

Abstract

The present invention belongs to the technical field of adhesives, and specifically relates to a high-frequency adhesive for flexible copper-clad laminates and a preparation method thereof. The present invention uses low-molecular-weight polyphenylene ether as a phenol source, 1-(2-furan)cyclopropylamine as an amine source, synthesizes benzoxazine functionalized polyphenylene ether, uses 4,4'-dioxyphthalic anhydride, 3,5-diaminobenzoic acid and 1,3-bis(4-aminophenoxy)benzene to react at room temperature, and obtains a modified polyimide containing a carboxyl structure, which effectively improves the thermal performance of the high-frequency adhesive; glass wool fiber and mesoporous silica are selected as fillers, which can effectively reduce the polarized molecules in the unit volume of the high-frequency adhesive, and effectively reduce the dielectric constant and dielectric loss.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of adhesives, and in particular relates to a high-frequency adhesive for a flexible copper-clad laminate and a preparation method thereof. Background Art

[0002] Flexible copper clad laminate refers to a copper clad laminate formed by bonding copper foil to one or both sides of a flexible insulating material such as polyester film or polyimide film through a certain process. Flexible copper clad laminate is used in aerospace equipment, navigation equipment, aircraft instruments, military guidance systems, and electronic products such as mobile phones, digital cameras, digital video cameras, automotive satellite positioning devices, LCD TVs, and laptops. Soft copper foil substrates are divided into two categories: adhesive-type three-layer flexible board substrates (3L-FCCL) and new adhesive-free two-layer flexible board substrates (2L-FCCL). The adhesive-type three-layer flexible board substrate is composed of three different materials: copper foil, film, and adhesive. It is also called a three-layer flexible copper clad laminate. It has the characteristics of good bonding effect and better flexibility. It is the mainstream product in the flexible copper clad laminate market.

[0003] At present, the commonly used adhesive in flexible copper clad laminates is a high-temperature curing epoxy system adhesive. However, as the functional integration of terminal application products becomes stronger and stronger, the high speed of flexible copper clad laminates becomes more and more important. The performance of flexible copper clad laminates in special environments and functional applications requires that it has higher weather resistance and bending resistance on the basis of good basic properties such as low dielectric constant and low dielectric loss. However, the flexible copper clad laminates made with existing adhesives have a high dielectric constant and poor heat resistance, resulting in high dielectric loss and short service life. Therefore, it is an urgent problem to be solved by personnel in this technical field to develop an adhesive that produces a flexible copper clad laminate with the characteristics of low dielectric constant, small thermal expansion and high bonding strength.

[0004] A Chinese patent application document with publication number CN109868102A discloses a modified epoxy resin adhesive for LCP-based flexible copper-clad laminates, comprising the following components: 75-150 parts of epoxy resin, 10-25 parts of toughening agent, 2-10 parts of curing agent, 0.1-1 part of accelerator, 1-2 parts of surface additive, 10-25 parts of filler and 100-200 parts of solvent. By adding surface additives to the adhesive, the surface tension of the adhesive on the LCP film is further reduced, the wettability is increased, and the flow of the adhesive is facilitated, but the thermal expansion of this adhesive is large.

[0005] The Chinese patent application document with publication number CN106633637A discloses a flexible thermally conductive resin for metal-based copper-clad laminates, the formula of which includes epoxy resin, thermoplastic elastomer, curing agent, catalyst, coupling agent and aluminum oxide, and the coupling agent used is a mixture of a silane coupling agent and one or more selected from titanate coupling agents, chromium complex coupling, aluminum zirconium coupling agents, magnesium coupling agents and tin coupling agents. This resin has excellent thermal conductivity and insulation properties, and has strong flexibility and bonding properties, and can improve the service life of the copper-clad laminate, but its dielectric constant is relatively large. Summary of the invention

[0006] In order to solve the technical problems of poor heat resistance and high dielectric loss existing in the related art, the object of the present invention is to provide a high-frequency adhesive for a flexible copper clad laminate and a preparation method thereof.

[0007] In order to achieve the above object, the technical solution of the present invention is as follows:

[0008] A high-frequency adhesive for a flexible copper-clad laminate comprises the following components in parts by weight:

[0009] 40-45 parts of a resin composition, 15-20 parts of a toughening agent, 5-8 parts of a curing agent, 10-15 parts of a flame retardant, and 5-8 parts of a filler; the resin composition is composed of modified benzoxazine, bismaleimide, and modified polyimide in a mass ratio of 4-8:1-3:6-10.

[0010] In the present invention, modified benzoxazine, bismaleimide and modified polyimide are used as resin compositions to prepare high-frequency adhesives, wherein the polyimide molecular chain contains an imide ring, has high heat resistance and low dielectric constant, benzoxazine has low molecular polarity, has low dielectric constant and dielectric loss, bismaleimide resin has excellent high temperature resistance and moisture resistance, and has a high glass transition temperature, which can improve the thermal stability of high-frequency adhesives. In the present invention, benzoxazine and polyimide are modified, and together with bismaleimide, a resin composition is formed, and the thermal performance and dimensional stability of the prepared high-frequency adhesive are improved, thereby improving the service life of the flexible copper clad laminate.

[0011] Furthermore, the preparation method of the modified benzoxazine is: dissolving poly 2,6-dimethyl-1,4-phenylene ether and bisphenol A in toluene, heating, adding benzoyl peroxide dropwise under stirring, keeping the temperature for reaction, then adding 1-(2-furan)cyclopropylamine and polyformaldehyde, reflux reaction, cooling, and obtaining the modified benzoxazine.

[0012] In the present invention, bisphenol A is reacted with poly 2,6-dimethyl-1,4-phenylene oxide to obtain low molecular weight polyphenylene oxide as a phenol source, 1-(2-furan)cyclopropylamine is used as an amine source, and benzoxazine functionalized polyphenylene oxide is synthesized by a solvent method, which effectively improves the crosslinking degree and glass transition temperature of the modified benzoxazine, thereby improving the heat resistance of the high-frequency adhesive. In addition, poly 2,6-dimethyl-1,4-phenylene oxide has a lower dielectric constant and dielectric loss, higher tensile strength and bending strength, and can effectively improve the toughness and crosslinking density of the benzoxazine resin.

[0013] Furthermore, in the preparation method of modified benzoxazine, the mass ratio of poly 2,6-dimethyl-1,4-phenylene ether, bisphenol A and benzoyl peroxide is 4-7:1-3:2-4; the molar ratio of poly 2,6-dimethyl-1,4-phenylene ether, 1-(2-furyl)cyclopropylamine and polyformaldehyde is 1-2:1-2:3-5.

[0014] Furthermore, in the preparation method of the modified benzoxazine, the heating temperature is 80-85° C., the insulation reaction time is 7.8-8.2 h, the reflux reaction temperature is 80-85° C., and the reflux reaction time is 6.0-6.5 h.

[0015] Furthermore, the preparation method of the modified polyimide is: dissolving 3,5-diaminobenzoic acid and 1,3-bis(4-aminophenoxy)benzene in N-methylpyrrolidone in an oxygen-free environment, adding 4,4'-phenylenedioxydiphthalic anhydride three times, stirring and reacting for 22-24 hours to obtain the modified polyimide.

[0016] The invention adopts 4,4'-phenylenedioxydiphthalic anhydride, 3,5-diaminobenzoic acid and 1,3-bis(4-aminophenoxy)benzene to react at room temperature to prepare a modified polyimide containing a carboxyl structure, which effectively improves the intermolecular bonding force of the polyimide, thereby improving the thermal performance and dimensional stability of the high-frequency adhesive.

[0017] Furthermore, in the preparation method of the modified polyimide, the molar ratio of 4,4'-phenylenedioxydiphthalic anhydride, 3,5-diaminobenzoic acid and 1,3-bis(4-aminophenoxy)benzene is 1-3:4-7:5-8.

[0018] The invention controls the number of carboxyl groups in the molecular structure of the modified polyimide by changing the molar ratio of 4,4'-phenylenedioxydiphthalic anhydride, 3,5-diaminobenzoic acid and 1,3-bis(4-aminophenoxy)benzene, thereby adjusting the thermal properties and dimensional stability of the high-frequency adhesive.

[0019] Furthermore, the toughening agent is one of terminal hydroxyl nitrile rubber, terminal amino nitrile rubber, and styrene-butadiene rubber; the curing agent is one of diaminodiphenyl sulfone, 2-methylimidazole, and diethylenetriamine; and the flame retardant is one of triphenyl phosphate, phosphite, and ditolyl phosphate.

[0020] Furthermore, the filler is composed of glass wool fibers and mesoporous silica in a mass ratio of 5-8:1-3; the length of the glass wool fibers is 100-150 μm.

[0021] In the present invention, glass wool fibers and mesoporous silica are added to the high-frequency adhesive. The glass wool fibers and mesoporous silica have rich pore structures, which can effectively reduce the polarized molecules per unit volume of the high-frequency adhesive, and effectively reduce the dielectric constant and dielectric loss. However, since the mesoporous silica is in powder form and easily agglomerated, affecting the performance of the adhesive, it is necessary to strictly control the mass ratio of the glass wool fibers and the mesoporous silica.

[0022] The present invention also provides a method for preparing the high-frequency adhesive for flexible copper-clad laminates, which specifically comprises: mixing the resin composition evenly, adding a toughening agent, a curing agent, a flame retardant and a filler, and stirring evenly to obtain the high-frequency adhesive for flexible copper-clad laminates.

[0023] Compared with the prior art, the high-frequency adhesive for flexible copper-clad laminate and the preparation method thereof provided by the present invention have the following technical advantages:

[0024] (1) The high-frequency adhesive prepared by using modified benzoxazine, bismaleimide and modified polyimide as the resin composition in the present invention has a lower dielectric constant and dielectric loss, and improves the thermal stability of the high-frequency adhesive;

[0025] (2) In the present invention, low molecular weight polyphenylene ether is used as a phenol source and 1-(2-furan)cyclopropylamine is used as an amine source to synthesize benzoxazine functionalized polyphenylene ether by a solvent method, which effectively improves the crosslinking degree and glass transition temperature of the modified benzoxazine, thereby improving the thermal stability of the high-frequency adhesive;

[0026] (3) The present invention uses 4,4'-dioxyphthalic anhydride, 3,5-diaminobenzoic acid and 1,3-bis(4-aminophenoxy)benzene to react at room temperature to prepare a modified polyimide containing a carboxyl structure, which effectively improves the intermolecular bonding force of the polyimide, thereby improving the thermal properties and dimensional stability of the high-frequency adhesive;

[0027] (4) In the present invention, glass wool fiber and mesoporous silica are selected as fillers, which can effectively reduce the polarized molecules per unit volume of the high-frequency adhesive and effectively reduce the dielectric constant and dielectric loss. DETAILED DESCRIPTION

[0028] In order to make the purpose, technical solution and advantages of the present invention more clearly understood, the present invention is further described in detail below in conjunction with the embodiments. It should be understood that the specific embodiments described herein are only used to explain the present invention and are not used to limit the present invention.

[0029] In this specific embodiment, the preparation method of the high-frequency adhesive for flexible copper-clad laminates is: after the resin composition is evenly mixed, a toughening agent, a curing agent, a flame retardant and a filler are added, and the mixture is evenly stirred to obtain the high-frequency adhesive for flexible copper-clad laminates. The toughening agent is one of terminal hydroxyl nitrile rubber, terminal amino nitrile rubber, and styrene-butadiene rubber; the curing agent is one of diaminodiphenyl sulfone, 2-methylimidazole, and diethylenetriamine; the flame retardant is one of triphenyl phosphate, phosphite, and ditolyl phosphate.

[0030] Example 1

[0031] A high-frequency adhesive for a flexible copper-clad laminate comprises the following components in parts by weight:

[0032] 40 parts of a resin composition, 20 parts of hydroxy-terminated nitrile rubber, 8 parts of diaminodiphenyl sulfone, 15 parts of triphenyl phosphate, and 8 parts of a filler; the resin composition is composed of modified benzoxazine, bismaleimide, and modified polyimide in a mass ratio of 4:1:6.

[0033] The preparation method of the modified benzoxazine is as follows: poly-2,6-dimethyl-1,4-phenylene ether and bisphenol A are dissolved in toluene, heated to 80°C, benzoyl peroxide is added dropwise under stirring, the reaction is kept warm for 8.2 hours, and then 1-(2-furan)cyclopropylamine and polyformaldehyde are added, the reaction is refluxed at 80°C for 6.5 hours, and the modified benzoxazine is obtained; the mass ratio of the poly-2,6-dimethyl-1,4-phenylene ether, bisphenol A and benzoyl peroxide is 4:1:2; and the molar ratio of the poly-2,6-dimethyl-1,4-phenylene ether, 1-(2-furan)cyclopropylamine and polyformaldehyde is 1:1:3.

[0034] The preparation method of the modified polyimide is as follows: 3,5-diaminobenzoic acid and 1,3-bis(4-aminophenoxy)benzene are dissolved in N-methylpyrrolidone in an oxygen-free environment, 4,4'-phenylenedioxydiphthalic anhydride is added three times, and the reaction is stirred for 22 hours to obtain the modified polyimide; the molar ratio of the 4,4'-phenylenedioxydiphthalic anhydride, 3,5-diaminobenzoic acid and 1,3-bis(4-aminophenoxy)benzene is 1:4:5.

[0035] The filler is composed of glass wool fibers and mesoporous silica in a mass ratio of 5:1; the length of the glass wool fibers is 100 μm.

[0036] Example 2

[0037] A high-frequency adhesive for a flexible copper-clad laminate comprises the following components in parts by weight:

[0038] 45 parts of a resin composition, 15 parts of styrene-butadiene rubber, 5 parts of 2-methylimidazole, 10 parts of phosphite, and 5 parts of a filler; the resin composition is composed of modified benzoxazine, bismaleimide and modified polyimide in a mass ratio of 8:3:10.

[0039] The preparation method of the modified benzoxazine is as follows: poly 2,6-dimethyl-1,4-phenylene ether and bisphenol A are dissolved in toluene, heated to 85°C, benzoyl peroxide is added dropwise under stirring, the reaction is kept warm for 7.8 hours, and then 1-(2-furan)cyclopropylamine and polyformaldehyde are added, refluxed at 85°C for 6.0 hours, and cooled to obtain the modified benzoxazine; the mass ratio of the poly 2,6-dimethyl-1,4-phenylene ether, bisphenol A and benzoyl peroxide is 7:3:4; the molar ratio of the poly 2,6-dimethyl-1,4-phenylene ether, 1-(2-furan)cyclopropylamine and polyformaldehyde is 2:2:5.

[0040] The preparation method of the modified polyimide is as follows: 3,5-diaminobenzoic acid and 1,3-bis(4-aminophenoxy)benzene are dissolved in N-methylpyrrolidone in an oxygen-free environment, 4,4'-dioxyphthalic anhydride is added three times, and the reaction is stirred for 24 hours to obtain the modified polyimide; the molar ratio of the 4,4'-dioxyphthalic anhydride, 3,5-diaminobenzoic acid and 1,3-bis(4-aminophenoxy)benzene is 3:7:8.

[0041] The filler is composed of glass wool fibers and mesoporous silica in a mass ratio of 8:3; the length of the glass wool fibers is 150 μm.

[0042] Example 3

[0043] A high-frequency adhesive for a flexible copper-clad laminate comprises the following components in parts by weight:

[0044] 42 parts of a resin composition, 18 parts of amino-terminated nitrile rubber, 7 parts of diethylenetriamine, 12 parts of ditolyl phosphate, and 7 parts of a filler; the resin composition is composed of modified benzoxazine, bismaleimide and modified polyimide in a mass ratio of 6:2:9.

[0045] The preparation method of the modified benzoxazine is as follows: poly 2,6-dimethyl-1,4-phenylene ether and bisphenol A are dissolved in toluene, heated to 83° C., benzoyl peroxide is added dropwise under stirring, the reaction is kept warm for 8.0 hours, and then 1-(2-furan)cyclopropylamine and polyformaldehyde are added, the reaction is refluxed at 83° C. for 6.3 hours, and the modified benzoxazine is obtained; the mass ratio of the poly 2,6-dimethyl-1,4-phenylene ether, bisphenol A and benzoyl peroxide is 5:2:3; and the molar ratio of the poly 2,6-dimethyl-1,4-phenylene ether, 1-(2-furan)cyclopropylamine and polyformaldehyde is 1:2:4.

[0046] The preparation method of the modified polyimide is as follows: 3,5-diaminobenzoic acid and 1,3-bis(4-aminophenoxy)benzene are dissolved in N-methylpyrrolidone in an oxygen-free environment, 4,4'-dioxyphthalic anhydride is added three times, and the reaction is stirred for 23.5 hours to obtain the modified polyimide; the molar ratio of the 4,4'-dioxyphthalic anhydride, 3,5-diaminobenzoic acid and 1,3-bis(4-aminophenoxy)benzene is 2:5:7.

[0047] The filler is composed of glass wool fibers and mesoporous silica in a mass ratio of 7:2; the length of the glass wool fibers is 120 μm.

[0048] Comparative Example 1

[0049] This comparative example is similar to Example 3, and the difference between this comparative example and Example 3 is that the resin composition in this comparative example is composed of modified benzoxazine, bismaleimide and modified polyimide in a mass ratio of 1:9:2.

[0050] Comparative Example 2

[0051] This comparative example is similar to Example 3, and the difference between this comparative example and Example 3 is that an equal amount of cyanate ester is used to replace bismaleimide resin in this comparative example.

[0052] Comparative Example 3

[0053] This comparative example is similar to Example 3, and the difference between this comparative example and Example 3 is that an equal amount of benzoxazine is used in this comparative example instead of modified benzoxazine.

[0054] Comparative Example 4

[0055] This comparative example is similar to Example 3, and the difference between this comparative example and Example 3 is that an equal amount of polyimide is used instead of modified polyimide in this comparative example.

[0056] Comparative Example 5

[0057] This comparative example is similar to Example 3, and the difference between this comparative example and Example 3 is that in the preparation method of the modified benzoxazine in this comparative example, an equal amount of aniline is used instead of 1-(2-furanyl)cyclopropylamine.

[0058] Comparative Example 6

[0059] This comparative example is similar to Example 3, and the difference between this comparative example and Example 3 is that in the preparation method of the modified polyimide in this comparative example, an equal amount of 1,3-bis(4-aminophenoxy)benzene is used to replace 3,5-diaminobenzoic acid.

[0060] Comparative Example 7

[0061] This comparative example is similar to Example 3, and the difference between this comparative example and Example 3 is that the molar ratio of 4,4'-phenylenedioxydiphthalic anhydride, 3,5-diaminobenzoic acid and 1,3-bis(4-aminophenoxy)benzene in the preparation method of the modified polyimide in this comparative example is 8:1:3.

[0062] Comparative Example 8

[0063] This comparative example is similar to Example 3, and the difference between this comparative example and Example 3 is that an equal amount of mesoporous silica is used in the filler of this comparative example instead of glass wool fiber.

[0064] Test example

[0065] The high-frequency adhesives obtained in Examples 1 to 3 and Comparative Examples 1 to 8 were coated on one side of the polyimide film, and baked at 130°C for 5 minutes to remove the solvent, and then the release layer was coated at 80°C to obtain a protective film for a high-frequency copper-clad laminate. Referring to IPC-TM-650, the high-frequency copper-clad laminate protective films obtained by using the high-frequency adhesives obtained in Examples 1 to 3 and Comparative Examples 2 to 7 were subjected to heat resistance tests, immersed in a tin furnace at a temperature of 288°C for 30 seconds, and after taking out the test pieces, the surface was observed for bubbling, discoloration, floating, and peeling. The dielectric constant and dielectric loss tests were performed on the high-frequency copper-clad laminate protective films obtained by using the high-frequency adhesives obtained in Examples 1 to 3, Comparative Examples 1 and 8. The test results are shown in Table 1.

[0066] Table 1

[0067]

[0068] As shown in Table 1, the high-frequency copper-clad laminate protective film prepared by the high-frequency adhesive provided by the present invention was immersed in a tin furnace at a temperature of 288°C for 30 seconds. After the test piece was taken out, no bubbling, discoloration, floating and peeling occurred on the surface, which shows that the high-frequency adhesive provided by the present invention has good heat resistance; the high-frequency copper-clad laminate protective film prepared by the high-frequency adhesive provided by the present invention has a dielectric constant of 2.49-2.65 and a dielectric loss of 0.00041-0.00057, which shows that the high-frequency adhesive provided by the present invention has good dielectric properties. Among them, the high-frequency adhesive prepared in Example 3 has the best performance and is the best embodiment of the present invention.

[0069] Compared with Example 3, Comparative Example 1 changes the mass ratio of the components in the resin composition, but the dielectric properties of the obtained protective film for high-frequency copper clad laminates deteriorate, which indicates that the components in the resin composition of the present invention are one of the key factors for controlling dielectric properties and heat resistance, and the resin composition provided by the present invention is already in the optimal range, and changing the mass ratio of the components will lead to reduced performance; Comparative Example 2 uses an equal amount of cyanate ester to replace the bismaleimide resin, but the heat resistance of the obtained protective film for high-frequency copper clad laminates deteriorates, which indicates that the bismaleimide resin in the resin composition can effectively improve the thermal stability of the high-frequency adhesive; Comparative Example 3 uses an equal amount of benzoxazolyl glycol ether to replace the bismaleimide resin. In Example 4, an equal amount of polyimide was used to replace the modified polyimide, and in Example 5, an equal amount of aniline was used to replace 1-(2-furan)cyclopropylamine, but the heat resistance of the protective film for the high-frequency copper-clad laminate obtained was poor, which shows that the modification of benzoxazine in the present invention effectively improves the heat resistance of the high-frequency adhesive; in Example 4, an equal amount of polyimide was used to replace the modified polyimide, and in Example 5, an equal amount of aniline was used to replace 1-(2-furan)cyclopropylamine, but the heat resistance of the protective film for the high-frequency copper-clad laminate obtained was poor, which shows that the modification of polyimide in the present invention improves the heat resistance of the high-frequency adhesive, and 1-(2-furan)cyclopropylamine is the key to improving the heat resistance of the high-frequency adhesive, which is because the furan ring of 1-(2-furan)cyclopropylamine will react with the Mannich ring generated by the ring opening of the oxazine ring. The bridge undergoes a cross-linking reaction, and the oxygen atom in the furan ring can form a hydrogen bond with the phenolic hydroxyl group to improve the thermal properties of the resin; Comparative Example 6 uses an equal amount of 1,3-bis(4-aminophenoxy)benzene instead of 3,5-diaminobenzoic acid, but the heat resistance of the obtained high-frequency copper clad laminate protective film becomes worse, which shows that 3,5-diaminobenzoic acid can introduce carboxyl groups into the molecular structure of polyimide, and the carboxyl groups can increase the binding force between polyimide molecules, thereby improving the thermal properties of the high-frequency adhesive; Comparative Example 7 changes the molar ratio of 4,4'-phenylenedioxydiphthalic anhydride, 3,5-diaminobenzoic acid and 1,3-bis(4-aminophenoxy)benzene, but the obtained The heat resistance of the protective film for high-frequency copper-clad laminates deteriorates, which indicates that the molar ratio of 4,4'-dioxyphthalic anhydride, 3,5-diaminobenzoic acid and 1,3-bis(4-aminophenoxy)benzene provided by the present invention has been optimized; Comparative Example 8 uses an equal amount of mesoporous silica instead of glass wool fiber, but the dielectric properties of the obtained protective film for high-frequency copper-clad laminates deteriorate, which indicates that the glass wool fiber and mesoporous silica have a synergistic effect of 1+1>2, which can effectively reduce the polarized molecules per unit volume of the high-frequency adhesive, effectively reduce the dielectric constant and dielectric loss, and excessive addition of mesoporous silica will affect the dielectric properties of the high-frequency adhesive.

[0070] The above description is only a preferred specific implementation manner of the present invention, but the protection scope of the present invention is not limited thereto. Any changes or substitutions that can be easily conceived by any technician familiar with the technical field within the technical scope disclosed by the present invention should be covered within the protection scope of the present invention.

Claims

1. A high-frequency adhesive for a flexible copper-clad laminate, characterized in that: The composition comprises the following components in parts by weight: 40-45 parts of a resin composition, 15-20 parts of a toughening agent, 5-8 parts of a curing agent, 10-15 parts of a flame retardant, and 5-8 parts of a filler; the resin composition is composed of modified benzoxazine, bismaleimide resin, and modified polyimide in a mass ratio of 4-8:1-3:6-10; The preparation method of the modified benzoxazine comprises: dissolving poly-2,6-dimethyl-1,4-phenylene ether and bisphenol A in toluene, heating, adding benzoyl peroxide dropwise under stirring, keeping the temperature for reaction, then adding 1-(2-furanyl)cyclopropylamine and polyformaldehyde, refluxing for reaction, cooling, and obtaining the modified benzoxazine; The preparation method of the modified polyimide is as follows: 3,5-diaminobenzoic acid and 1,3-bis(4-aminophenoxy)benzene are dissolved in N-methylpyrrolidone in an oxygen-free environment, 4,4'-phenylenedioxydiphthalic anhydride is added three times, and the mixture is stirred for reaction for 22-24 hours to obtain the modified polyimide; The filler is composed of glass wool fiber and mesoporous silica in a mass ratio of 5-8:1-3.

2. The high-frequency adhesive for flexible copper-clad laminate according to claim 1, characterized in that: In the preparation method of modified benzoxazine, the mass ratio of poly 2,6-dimethyl-1,4-phenylene ether, bisphenol A and benzoyl peroxide is 4-7:1-3:2-4; the molar ratio of poly 2,6-dimethyl-1,4-phenylene ether, 1-(2-furan)cyclopropylamine and polyformaldehyde is 1-2:1-2:3-5.

3. The high-frequency adhesive for flexible copper-clad laminate according to claim 1, characterized in that: In the preparation method of modified benzoxazine, the heating temperature is 80-85° C., the insulation reaction time is 7.8-8.2 hours, the reflux reaction temperature is 80-85° C., and the reflux reaction time is 6.0-6.5 hours.

4. The high-frequency adhesive for flexible copper-clad laminate according to claim 1, characterized in that: In the preparation method of the modified polyimide, the molar ratio of 4,4'-phenylenedioxydiphthalic anhydride, 3,5-diaminobenzoic acid and 1,3-bis(4-aminophenoxy)benzene is 1-3:4-7:5-8.

5. The high-frequency adhesive for flexible copper-clad laminate according to claim 1, characterized in that: The toughening agent is one of terminal hydroxyl nitrile rubber, terminal amino nitrile rubber, and styrene-butadiene rubber; the curing agent is one of diaminodiphenyl sulfone, 2-methylimidazole, and diethylenetriamine; and the flame retardant is one of triphenyl phosphate, phosphite, and ditolyl phosphate.

6. The high-frequency adhesive for flexible copper-clad laminate according to claim 1, characterized in that: The length of the glass wool fibers is 100-150 μm.

7. The method for preparing a high-frequency adhesive for a flexible copper-clad laminate according to any one of claims 1 to 6, characterized in that: Specifically, the resin composition is mixed evenly, and then a toughening agent, a curing agent, a flame retardant and a filler are added, and the mixture is stirred evenly to obtain the high-frequency adhesive for the flexible copper-clad laminate.

Citation Information

Patent Citations

  • Flexible heat-conducting resin for metal-based copper-cladded plate

    CN106633637A

  • Modified epoxy resin adhesive for LCP-based flexible copper clad laminate and preparation method and application

    CN109868102A

  • Copolymer film forming resin containing benzoxazine structure and deep UV negativity chemical amplification type photo resist

    CN101463106A

  • Modified polyimide resin, adhesive composition containing modified polyimide resin and covering film containing adhesive composition

    CN103483586A